Dietary behaviors and survival in people with head and neck cancer: Results from Head and Neck 5000. Issue 7 (30th January 2019) - Lang, Samantha; Schimansky, Sarah; Beynon, Rhona; Penfold, Christopher; Davies, Amy; Waylen, Andrea; Thomas, Steven; Pring, Miranda; Pawlita, Michael; Waterboer, Tim; Ness, Andrew R.
Abstract: Background: The association between diet and head and neck cancer (HNC) survival is unclear. Methods: Cox proportional hazard models measured the association between fruit, vegetable, and deep‐fried food intake and HNC overall survival adjusting for clinical, social and lifestyle variables including smoking, alcohol, and HPV status. Results: Fruit and vegetable intake and improved survival were associated in minimally adjusted analyses. Following adjustment for smoking and alcohol consumption (fully adjusted analyses), the association with survival disappeared for fruit (HR 0.91, 95% CI 0.67, 1.23; P for trend = .55) and attenuated for vegetables (HR 0.79, 95% CI 0.61, 1.03; P for trend = .04). We observed no association between survival and deep‐fried food intake in minimally adjusted or fully adjusted analyses (HR 0.88 95% CI 0.72, 1.07; P for trend = .13). Conclusions: Vegetable intake and HNC survival are modestly associated. There is some confounding by tobacco and alcohol consumption.